Malaysian Islamic Party (PAS) and Challenges in Johor - Sabtu, Muhamad Helmy; Nordin, Shah Rul Anuar; Mohamad Suhaimy, Khairul Azman (Journal of Techno-Social, 2022)
PAS’s existence in the state of Johor has spanned more than six decades. Nevertheless, the party’s performance in the state election is seen to be still in an uncertain state until today when it failed to win a satisfactory number of seats both at the parliamentary and state assembly levels. This situation suggests that PAS is facing a serious problem that needs attention and a thorough solution to enable the party to get out of the prolonged political lethargy syndrome. By using a descriptive case study design, this article aims to unravel the challenges faced by Islamic party that make it difficult for them to expand in the state of Johor. The results of the study show that there are three main challenges faced by PAS, namely limitations on religious access, party identification and current sentiment of oppositional politics that are not in their favor. Therefore, PAS is advised to rejuvenate its image and set the direction of the party clearly so that the penetration rate of the party’s influence can be increased in the state of Johor.